Interactive transmission of two phytoplasmas by the vector insect. (19th August 2014) - Rashidi, M.; D'Amelio, R.; Galetto, L.; Marzachì, C.; Bosco, D.
Abstract Phytoplasmas are wall‐less bacteria associated with many plant diseases of wild and cultivated plants, transmitted by hemipteran insects. In nature, vectors can acquire more than one phytoplasma by feeding on multiple‐infected source plants or sequentially on plants infected by different phytoplasmas. The acquisition of multiple phytoplasmas may lead to their interaction in the insects. In this work, nymphs of the leafhopper Euscelidius variegatus were allowed to feed sequentially on Flavescence dorée (FDP)‐infected and chrysanthemum yellows (CYP)‐infected source plants and vice‐versa. Following the acquisition feeding, the titre of the two phytoplasmas in the insect was measured over time. FDP and CYP transmission capability of the doubly infected leafhoppers was studied by transmission to Vicia faba and to artificial feeding medium. Both phytoplasmas were acquired by the vector regardless of the feeding order and FDP titre, but not CYP titre, was affected by double infection. FDP and CYP persisted in the insect for life. Only CYP was consistently and efficiently transmitted by doubly infected leafhoppers. Consistently, FDP was seldom detected in the salivary glands and never in the artificial feeding medium of doubly infected leafhoppers. In conclusion, competition between CYP and FDP affected only salivary gland colonisation, while it had almost no effect on phytoplasma acquisition. Competition among phytoplasma strains in an evolutionary time scale may explain the greater ability of CYP to colonise the insect body and be transmitted.